Expanded mixed finite element method for second order hyperbolic equations. (15th October 2019) - Wang, Keyan; Wang, Qisheng
Abstract: In this paper, an expanded mixed finite element method is developed to approximate the solution of second order hyperbolic equations. We discuss and theoretically prove the existence and uniqueness of solution for the semidiscrete formulation, and obtain the optimal order error estimates in the L ∞ ( L 2 ) norm. In addition, we also construct the fully discrete approximations and provide the corresponding error analysis. Some numerical examples are presented to demonstrate the theoretical analysis.